Explorando a relação de Euler: um relato de experiência com oficinas educativas no ensino de geometria espacial - Silva, Alessandro Ferreira da (2025)
The teaching of Spatial Geometry in Brazil faces challenges related to the lack of appropriate teaching methodologies, often failing to systematically explore visualization, construction, and manipulation of three-dimensional forms and objects, hindering students' learning process. The predominance of traditional and theoretical approaches, usually employing two-dimensional representations of three-dimensional figures on media such as blackboards or textbooks, contributes to student demotivation and difficulty in developing spatial reasoning. Based on studies developed in the field of education and mathematics teaching, this research investigates the impact of educational workshops on the teaching of Spatial Geometry with 9th-grade students at Dalka Leles Municipal School, in Goiânia. The methodology adopted is qualitative, focusing on practical activities and manipulable materials to explore concepts such as faces, vertices, and edges of polyhedra, as well as Euler’s relation identified in convex polyhedra in general. It is expected that this research will contribute to the adoption of more dynamic and interactive methodologies, fostering more effective learning and stimulating student interest in mathematics.